2008
DOI: 10.1096/fasebj.22.1_supplement.412.3
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years Since the Discovery of PKA

Abstract: In 1968, after Sutherland's discovery of cAMP, Krebs discovered cAMP‐dependent Protein Kinase (PKA), thus establishing the major paradigm for cAMP signaling in mammalian cells. The protein kinases, one of the largest gene families, are associated with many diseases, and PKA serves as a prototype for general protein kinase structure and function. While the structure of PKA first defined the conserved protein kinase fold, the recent solution of inhibited complexes of the catalytic (C) and regulatory (R) subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To study the molecular make-up of the signaling pathways activated by cargo, given the robust and general role of PKA in ER export, we considered that AKAP (A kinase-anchoring protein) scaffold-based signaling complexes may provide a suitable model. AKAPs are scaffolds that anchor PKA-dependent pathways and other regulatory proteins onto specific cellular structures, often forming large signaling complexes (Scott et al, 2013;Taylor et al, 2008;Wong and Scott, 2004). To elucidate the specific components and organization of the AKAP-based AREX signaling system, we used a series of concatenated folding pulse experiments.…”
Section: Molecular Composition and Organization Of The Arex Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the molecular make-up of the signaling pathways activated by cargo, given the robust and general role of PKA in ER export, we considered that AKAP (A kinase-anchoring protein) scaffold-based signaling complexes may provide a suitable model. AKAPs are scaffolds that anchor PKA-dependent pathways and other regulatory proteins onto specific cellular structures, often forming large signaling complexes (Scott et al, 2013;Taylor et al, 2008;Wong and Scott, 2004). To elucidate the specific components and organization of the AKAP-based AREX signaling system, we used a series of concatenated folding pulse experiments.…”
Section: Molecular Composition and Organization Of The Arex Signalingmentioning
confidence: 99%
“…Cargo Folding Activates and Recruits PKA at the ERESs PKA is comprised of homo-dimers of catalytic and regulatory subunits. The latter bind to a conserved motif in the AKAPs and are activated upon binding cAMP (Carr et al, 1992;Scott et al, 2013), which is followed by detachment of the catalytic subunits (Cancino et al, 2014;Taylor et al, 2008). We found that, in cells kept at 40 C to accumulate unfolded cargo, PKA does not reside at the ERESs; the regulatory subunit PKA-RIIa localizes mainly in an uncharacterized cluster of perinuclear puncta that does not co-stain for the ERES marker Sec31A (Figure 4A,left) and the catalytic subunit PKA-Ca shows a diffuse distribution ( Figure S3A, left).…”
Section: Molecular Composition and Organization Of The Arex Signalingmentioning
confidence: 99%